1986
DOI: 10.1042/bj2350057
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and biosynthesis of membrane proteins of lipid bodies in the scutella of maize (Zea mays L.)

Abstract: Storage lipid bodies, which are prominent organelles present in the storage tissues of most seeds, have not been subjected to intensive biochemical investigation. In the present studies the major proteins in lipid bodies isolated from eleven taxonomically diverse species were shown to be distinctly different, as revealed by SDS/polyacrylamide-gel electrophoresis. The lipid-body membrane of maize (Zea mays L.) contained three major proteins of low Mr (19,500, 18,000 and 16,500), and they were chosen for further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
41
0
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(44 citation statements)
references
References 23 publications
2
41
0
1
Order By: Relevance
“…Enlargement ofthe vesicle eventually produces a lipid body which is composed of a bag of triacylglycerol surrounded by a half-unit membrane of phospholipids and proteins. Earlier, we showed that the lipid body membrane proteins are synthesized on the RER (16). The localization of diacylglycerol acyltransferase, the last enzyme of triacylglycerol biosynthesis, in the ER further supports the ER vesiculation model.…”
supporting
confidence: 76%
“…Enlargement ofthe vesicle eventually produces a lipid body which is composed of a bag of triacylglycerol surrounded by a half-unit membrane of phospholipids and proteins. Earlier, we showed that the lipid body membrane proteins are synthesized on the RER (16). The localization of diacylglycerol acyltransferase, the last enzyme of triacylglycerol biosynthesis, in the ER further supports the ER vesiculation model.…”
supporting
confidence: 76%
“…These lipid bodies contain a limited number of distinct proteins which are believed to be integrated in the surrounding monolayer (11). The protein termed L3 (Mr 16,500) and lipase (Mr 65,000) are the best studied (8,9,11,13 Plant Materials. Kernels of inbred maize (Zea mays L. cv Mo 17) were obtained from the Illinois Foundation Seed Corp., (Champaign, IL).…”
Section: Methodsmentioning
confidence: 99%
“…The lipid bodies in scutella of maize kernels have been studied the most extensively. These lipid bodies contain a limited number of distinct proteins which are believed to be integrated in the surrounding monolayer (11). The protein termed L3 (Mr 16,500) and lipase (Mr 65,000) are the best studied (8,9,11,13 Plant Materials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Current evidence suggests that oleosin targets to the ER by an SRP-mediated pathway; oleosin mRNA is found in ERbound polyribosomes (27), and exogenous SRP inhibits oleosin translation in vitro (28). Oleosin expression in yeast mutants also indicates a requirement for SRP and Sec61 (29).…”
mentioning
confidence: 99%